Salt lakes separated from the White Sea ... - Krasnova, Elena; Voronov, Dmitry; Frolova, Natalia; Pantyulin, Anatoly; Samsonov, Timofey (EARSeL eProceedings, 2015)
Many lakes at different stages of separation from the sea were formed along the coast of Kandalakshsky Gulf of the White Sea because of a rapid glacioisostatic lifting. The natural stage of their hydrological evolution is the meromixis. Five stratified lakes at different stages of isolation were studied in 2010-2014. The studies included echo-sounding of bottom topography, measurements of hydrological parameters: temperature, salinity, pH, redox potential, oxygen content, as well as registration of organoleptic properties of water, and in situ illumination measurements at different depths. Data from four years of observation are generalized, the vertical structure of the lakes was determined, as well is its seasonal and interannual variations. The lakes are ranked by chronology of their separation from the sea. ...